Stage‐matched survival differences by ethnicity among gastric cancer patients of Asian ancestry treated in the United States. Issue 6 (29th January 2019) - Rhome, Ryan M.; Ru, Meng; Moshier, Erin; Mazumdar, Madhu; Buckstein, Michael H.
Abstract : Background: Differences have been noted in overall survival (OS) in gastric cancer (GC) between trials conducted in Western vs Asian countries. The National Cancer Database (NCDB) reports outcomes and patient/disease variables relevant to OS. Methods: Using NCDB, we identified 89 558 adult patients with GC diagnosed (2004‐2012), where self‐reported race/ethnicity was available. Cox proportional hazard model was used to calculate multivariable hazard ratio (HR) of death, adjusting for race/ethnicity, age, gender, insurance, histology, grade, location, stage, and treatment type. Results: After adjustment, Asian patients had improved OS (HR = 0.74, 95% confidence intervals [CI] = 0.71‐0.77). There were differences in OS between Asian ethnicities compared with white patients (n = 69 945), notably with Korean (n = 1249, HR = 0.70, 95% CI = 0.64‐0.75), Chinese (n = 1271, HR = 0.69, 95% CI = 0.64‐0.75), and Indian/Pakistani patients (n = 492, HR = 0.68, 95% CI = 0.61‐0.76). Japanese (n = 829, HR = 0.84, 95% CI = 0.77‐0.91) and Vietnamese (n = 560, HR = 0.79, 95% CI = 0.71‐0.88) OS was also improved ( P < 0.0001), while Filipino patients showed no difference (n = 415, HR = 1.00). Black patients had slightly improved OS (n = 13 500, HR = 0.98, 95% CI = 0.95‐1.00, P = 0.035). Conclusions: This analysis supports improved OS in Asian patients independent of stage, treatment, and known patient or disease characteristics in this large US cohort, and is the largest to define OS differences between Asian ethnicities.